Remission death in acute lymphoblastic leukaemia: a changing pattern. - Atra, A; Richards, S; Chessells, J (1993)
The pattern of remission deaths was examined in 842 children with acute lymphoblastic leukaemia (ALL) treated at a single centre over 18 years. The mortality rate from leukaemia fell significantly during three consecutive time periods during which treatment became progressively more intensive and that during remission induction fell from 3.5% to under 1%, but the rate of death in remission stayed constant at 5-6%. The factors associated with an increased risk of remission death were: young age, a higher leucocyte count, bone marrow transplantation, and Down's syndrome. The pattern of remission deaths changed over the years; measles and herpes viruses decreased while deaths associated with periods of intensification and gut toxicity increased. Four children developed second neoplasms. Treatment of ALL is still associated with a significant risk of death in remission but the pattern of infective deaths has changed. Many should be avoidable by provision of adequate supportive care, close supervision after periods of intensive treatment, and appropriate antibiotic, antifungal, and cytokine therapy.